Do Innovation and Creativity Product Food and Beverage for Marketing Performance of MSMEs? The Role of Competitive Advantage - Sudarmiatin; Diana Ambarwati; Ludi Wishnu Wardana (International Journal of Business and Applied Economics, 2023)
This study intends to ascertain how food and beverage product innovation and creativity affect marketing performance via competitive advantage for MSMEs that are Aspemtari members. A questionnaire was used to collect data for this study, which was conducted using a quantitative methodology. Members of MSMEs make up both the population and sample in this study. The Aspemtari person has 45 members. Sampling method utilizing saturated samples and SmartPls analysis as a support tool. The findings of this study, product innovation has a positive and significantly effect on competitive advantages. However, creative output does not significantly and negatively effect competitive advantage. Innovation product and innovation and creativity product not has a positive and significant effect on marketing performance. Competitive advantage has an effect positive and significant on marketing performance Aspemtari MSMEs.